SISTEM INFORMASI PENDISTRIBUSIAN BANTUAN BENIH UNGGUL DAN ALAT MESIN PERTANIAN KEPADA KELOMPOK TANI DI DINAS PERTANIAN KABUPATEN SERANG - Edy Rakhmat; Huswatun Hasanah; Tri Nanda Wiguna Omansa (Journal of Innovation And Future Technology (IFTECH), 2022)
The Agriculture Department of Serang Regency designed a program of agricultural equipment assistance and direct assistance of superior seeds to overcome the problem of food security. However, data on farmer groups is not yet available accurately because so far the existing system has not provided a database-based program application. This causes problems, namely difficulties in the process of making reports to collect data and search for farmer group data. Delays in making reports often occur, and the distribution has not been right on target. To overcome and solve these problems, the researcher aims to develop an Information System for the Distribution of Superior Seeds and Agricultural Machine Tools to the Farmers Group at the Serang Regency Agriculture Service. Data collection techniques were carried out by field studies and literature studies. The field study uses observation and interviews. Literature study is carried out by reviewing various previous research articles that are in accordance with the research topic. In addition, this is also done by searching for documents, procedures and studying books and other written sources from libraries and other written literature related to research. With this information system, data creation on seed needs and requests for agricultural machinery can be done easily and quickly, reporting systems can be created at any time when reports are needed. In addition, data search can be done easily. Data redundancy or duplication can be minimized and the required reports can be printed immediately.